Cell morphology and nucleoid dynamics in dividing Deinococcus radiodurans - Kevin Floc’h (Nature Portfolio, 2019)
Deinococcus radiodurans is a relatively large spherical bacterium with a multipartite genome. Here, the authors study the coordinated morphological changes at the cellular and nucleoid level as the bacteria progress through the cell cycle, showing complex nucleoid organization and dynamics.